(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the social importance of the development of environmental education in the system of relations between man and nature is studied. Also, the priority tasks of forming ecologically conscious activities based on improving environmental education were analyzed. Along with modern innovative approaches in the solution of socio-ecological problems, the importance of an ecological approach based on the traditions of the use of nature by the local population is scientifically based. In addition to the improvement of the activities of education and promotion of ecological culture, scientific conclusions are given regarding the development of the scientific and theoretical foundations of the tendencies of restoring and developing the ecological values of the Uzbek people and deepening the theoretical, methodological and practical aspects of the possibilities of development.